Human fibronectin contains distinct adhesion- and motility-promoting domains for metastatic melanoma cells (The Rockefeller University Press, 1986)
The active migration of tumor cells through extracellular matrices has been proposed to play a role in certain aspects of metastasis. Metastatic tumor cells migrate in vitro in response to substratum-bound adhesive glycoproteins such as fibronectin. The present studies use affinity-purified proteolytic fragments of fibronectin to determine the nature of adhesion- and/or motility-promoting domains within the protein. Two distinct fragments were identified with cell adhesion- promoting activities. By a number of criteria, the adhesive activity promoted by these two fragments was distinct. One fragment, a 75-kD tryptic fragment purified by monoclonal antibody chromatography, promoted the adhesion, spreading, and haptotactic motility of melanoma cells. Experiments using a synthetic cell attachment peptide in solution indicated that at least part of the attachment activity exhibited by the 75-kD fragment is mediated by the sequence arg-gly-asp- ser. It was not possible to demonstrate migration-stimulating activity using a small (11.5 kD) peptic fragment containing this sequence (Pierschbacher, M.D., E. G. Hayman, and E. Ruoslahti, 1981, Cell, 26:259-267) suggesting that another cell-binding activity within the 75 kD fragment distinct from arg-gly-asp-ser might be required for motility. The second fragment that stimulated melanoma adhesion was a 33-kD tryptic/catheptic carboxyl-terminal heparin-binding fragment, which is localized to the A chain of fibronectin. This fragment promotes adhesion and spreading but not the motility of these cells. Melanoma adhesion to this heparin-binding fragment was sensitive to the effects of cycloheximide, which contrasted adhesion to the haptotaxis- promoting fragment. Importantly, these studies illustrate that haptotaxis in response to fibronectin is not due to simple adhesion gradients of this protein. The results are discussed in light of a model for multiple distinct cell surface constituents mediating cell adhesion and motility on fibronectin.